Burden of care in families of patients with early onset scoliosis. Issue 6 (November 2020) - Campbell, Megan; Matsumoto, Hiroko; St. Hilaire, Tricia; Roye, Benjamin D.; Roye, David P.; Vitale, Michael G.
Abstract : Early onset scoliosis is a complex manifestation of a heterogenous group of disorders, often necessitating multiple medical and surgical interventions to address the spinal deformity and its accompanying comorbidities. Current literature documents decreases in the health-related quality of life of these patients; however, there is a distinct lack of published data examining the burden on their caregivers. The purpose of this study is to compare burden on caregivers of children with early onset scoliosis and those on caregivers of age-matched healthy peers. A multicenter retrospective cohort study was conducted by querying a national registry for patients with early onset scoliosis diagnosed before 10 years old whose caregivers completed the caregiver burden (CB) and financial burden (FB) domains of the Early Onset Scoliosis Questionnaire (EOSQ-24) before their treatment. Scores were compared by etiology and planned treatment. The study identified 503 patients categorized by etiology and eventual treatment type. Overall, FB and CB scores for patients with early onset scoliosis were ≥10% worse than those of their age-matched peers, greater than the minimal clinically important difference for the EOSQ-24 ( P < 0.001). Non-idiopathic patients' scores were ≥16% worse than age-matched peers regardless of future treatment ( P < 0.001), while scores for idiopathic patients were varied. Idiopathic patients who went on to be observed had similar scores to national norms, but those who were managed either non-operatively (14% worse FB, 7% worse CB; P < 0.001) or operatively (25% worse FB, 27% worse CB; P > 0.05) had caregivers who reported greater burdens compared to those of healthy peers. This study suggests burdens on caregivers of patients with early onset scoliosis of nearly all etiologies are greater than those imposed on caregivers of healthy children, even before the additional stress of treatment is imposed. Level of evidence: II.